PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (PADA WAHYU ONDERSTEL SEMARANG) YOSEPHIN IMANIAR BUAYA NIM. 10.05.51.0078 PROGRAM STUDI S1 MANAJEMEN FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS STIKUBANK SEMARANG 2014 - Yosephin Imaniar Buaya, 10.05.51.0078; Indriyaningrum, Kis (Students Journal of Economic and Management, 2014)
This study is a study that tested the effect of Leadership and Work Environment on Employee Performance in Wahyu Onderstel. The research object in this paper is WahyuOnderstel Semarang. Sampling technique in this study is the use of data population of 53 respondents which means using the entire population by using the method of data collection questionnaire by distributing a list of statements to the respondents in order to obtain information. The data were analyzed using factor analysis to test the validity of the question items, Cronbach Alpha formula to test the reliability of the instrument, regression analysis, to examine the influence of each partial independent variables were tested with the coefficient of determination (RÂ²) and F test models. The results of the research are: (1) Leadership has not effect on the performance of employees, (2) The working environment has a positive and significant impact on employee performance.Keywords: Leadership, Workplace Environment and Employee Performance.